IMPLEMENTATION OF ZAKAT DISTRIBUTION OF ZAKAT FUNDS AT BINJAI CITY BAZNAS: IMPLEMENTASI PENDISTRIBUSIAN DANA ZAKAT PADA BAZNAS KOTA BINJAI - Mhd. Arbi Bayu Suhairi; Ansari Yamamah; Dhiauddin Tanjung (SOSIOEDUKASI, 2025)
Law No. 23 of 2011 concerning Zakat Management as a complement to the previous Law, namely Law No. 38 of 1999. This law provides institutional strengthening in the management of integrated zakat into a unified system. In turn, the National Amil Zakat Agency is the only institution that holds the authority of zakat, and the Amil Zakat Institution is a partner in assisting the National Amil Zakat Agency, as well as government supervision as a regulator. This research aims to answer the problem of how zakat is distributed according to the zakat law No. 23 of 2011 in Binjai City. How is zakat funds distributed according to law number 23 of 2011 and the perspective of Imam Shafi'i? How is the implementation of the distribution of zakat funds at BAZNAS Binjai City?. What is the perspective of law number 23 of 2011 and Imam Shafi'i's perspective on the system of distributing zakat funds at BAZNAS Binjai City? This research is a qualitative research using a legal science approach. The types of data used in this study are primary data, secondary data and the results of interviews with several administrators of the National Amil Zakat Agency of Binjai City. The results of the study show that the National Amil Zakat Agency in Binjai City in distributing zakat funds has not been running towards poverty alleviation in Binjai City. The lack of synergy to the distribution map that has not yet been seen makes the Binjai City National Amil Zakat Agency considered to need an effective breakthrough.